2002
DOI: 10.1097/00005768-200202000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in runners requiring on-site medical treatment at a single marathon

Abstract: This study found a 5.6% incidence of hyponatremia in marathon runners requiring medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…50,57,58,142,144 The early signs of EAH include headache, dizziness, physical exhaustion, muscular twitching, and nausea, all of which are also symptoms of hypohydration. Differential signs and symptoms of EAH due to fluid retention include weight gain, history of overdrinking, extremity swelling, and progressively worsening headache.…”
Section: Recognition Of Hypohydration and Fluid Overloadmentioning
confidence: 99%
“…50,57,58,142,144 The early signs of EAH include headache, dizziness, physical exhaustion, muscular twitching, and nausea, all of which are also symptoms of hypohydration. Differential signs and symptoms of EAH due to fluid retention include weight gain, history of overdrinking, extremity swelling, and progressively worsening headache.…”
Section: Recognition Of Hypohydration and Fluid Overloadmentioning
confidence: 99%
“…Of 15 marathon runners hospitalized with severe hyponatremia, 28.6% used NSAIDs (Davis et al 2001). In contrast, other observational studies have found no relationship between NSAIDs and hyponatremia (Hsieh et al 2002;Almond et al 2005;Scotney and Reid 2015). One inherent issue with existing literature is not knowing the NSAID type or dosage.…”
Section: Fluid and Electrolyte Balancementioning
confidence: 99%
“…Despite this information, few studies have examined this relationship, with most being observational studies with conflicting results (Davis et al 2001;Hsieh et al 2002;Almond et al 2005;Wharam et al 2006). Ultra-distance triathletes using NSAIDs had significantly lower post-race P[Na + ] compared with non-NSAID users (Wharam et al 2006).…”
Section: Fluid and Electrolyte Balancementioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drug (NSAID) use is common among marathon runners, being used in 50 to 60% of men and women, respectively (10,22,47). NSAID are known to potentiate the effects of arginine vasopressin (AVP) by inhibiting renal prostaglandin synthesis via the COX-2 isoform of cyclo-oxygenase (48 -50).…”
Section: Risk Factorsmentioning
confidence: 99%